Electrode catalyst layer for electrochemical cell, membrane electrode assembly for electrochemical cell, and electrochemical cell

JP7636391B2Active Publication Date: 2025-02-26MITSUI MINING & SMELTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022509959
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-27
Filing Date
2021-03-15
Publication Date
2025-02-26
Estimated Expiration
2041-03-15

Smart Images

  • Figure 0007636391000001
    Figure 0007636391000001
  • Figure 0007636391000002
    Figure 0007636391000002
Patent Text Reader

Abstract

An electrode catalyst layer for electrochemical cells comprises a first catalyst layer and a second catalyst layer. The cell resistance of the first catalyst layer is smaller than that of the second catalyst layer as measured at 80°C and 40% RH. The electrode catalyst layer for electrochemical cells is used in such a manner that the first catalyst layer can be arranged closer to an electrolytic membrane than the second catalyst layer. It is preferred that a first catalyst active component contained in the first catalyst layer and a second catalyst active component contained in the second catalyst layer independently contain at least one element selected from the group consisting of platinum, palladium, ruthenium and iridium.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode catalyst layer for an electrochemical cell, a membrane electrode assembly for an electrochemical cell, and an electrochemical cell. [Background technology]

[0002] In electrochemical cells such as solid polymer fuel cells and water electrolysis devices, a catalyst-supported carrier in which a precious metal catalyst such as platinum is supported on a carrier is used as an electrode catalyst layer. From the viewpoint of effective use of the catalyst, a carbonaceous material, which is a material with a large specific surface area, is often used as the catalyst carrier.

[0003] In recent years, it has been considered to operate electrochemical cells at medium temperatures of 100°C to 300°C in order to enhance catalytic activity. However, even in this temperature range or a lower temperature range of around 80°C, the carbonaceous material support tends to be oxidized and disappears, which is one of the causes of catalyst detachment and electrolyte membrane deterioration. As a means of improving the durability of the carbonaceous material support, the use of highly crystalline carbonaceous materials has been considered, but this is still not sufficient to improve durability. Therefore, the use of supports made of metal oxides instead of carbonaceous materials has been considered.

[0004] In the electrochemical cell described above, an electrode reaction occurs at the three-phase interface, and water is generated in the catalyst layer. The generated water dissipates from the catalyst layer, but in some cases accumulates in the catalyst layer. If this process progresses excessively, the catalyst layer will no longer be able to accommodate the water, resulting in the so-called flooding phenomenon. Patent Documents 1 and 2 propose methods for preventing the flooding phenomenon. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-171847 A [Patent Document 2] US2017 / 141407A1 Summary of the Invention

[0006] Since the above-mentioned metal oxide supports have higher polarity than carbonaceous material supports, the electrode reaction is less likely to proceed smoothly in extreme environments such as high humidity conditions that cause flooding, or low humidity conditions. As described above, techniques for improving the electrode reaction under high humidity conditions have been proposed, but no techniques have been proposed for improving the electrode reaction under both low and high humidity conditions.

[0007] Therefore, an object of the present invention is to provide an electrode catalyst layer for an electrochemical cell which is durable and allows electrochemical reactions to proceed smoothly under both low and high humidity conditions.

[0008] The present invention relates to a catalyst layer comprising a first catalyst-supported carrier in which a first catalytic active component is supported on a carrier containing a first metal oxide; and a second catalyst layer comprising a second catalyst-supported support in which a second catalytic active component is supported on a support containing a second metal oxide, The cell resistance of the first catalyst layer measured by the current interruption method at 80°C and 40% RH is lower than the cell resistance of the second catalyst layer. The present invention provides an electrode catalyst layer for an electrochemical cell, in which a first catalyst layer is disposed closer to the electrolyte membrane than a second catalyst layer.

[0009] The present invention relates to a catalyst layer comprising a first catalyst-supported carrier in which a first catalytic active component is supported on a carrier containing a first metal oxide; and a second catalyst layer comprising a second catalyst-supported support in which a second catalytic active component is supported on a support containing a second metal oxide, The volume cumulative particle size D of the first catalyst-supporting carrier at 50% cumulative volume by a laser diffraction / scattering particle size distribution measurement method 50 The volume cumulative particle size D at 50% cumulative volume of the second catalyst-supporting carrier measured by a laser diffraction / scattering particle size distribution measurement method50 Larger than The pore size distribution measured by mercury intrusion porosimetry was In the first catalyst layer, peaks are observed in the range of 0.005 μm or more and less than 0.1 μm and in the range of 0.1 μm or more and 1 μm or less, At least one peak is observed in the range of 0.005 μm or more and 0.1 μm or less in the second catalyst layer, The present invention provides an electrode catalyst layer for an electrochemical cell, in which a first catalyst layer is disposed closer to the electrolyte membrane than a second catalyst layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described below based on its preferred embodiments. The present invention relates to an electrode catalyst layer for an electrochemical cell. The electrode catalyst layer has at least two layers, a first catalyst layer and a second catalyst layer. The first catalyst layer and the second catalyst layer are preferably in direct contact with each other. In this case, no other catalyst layer or layer other than the catalyst layer is intentionally formed between the two catalyst layers. In the following description, the term "electrode catalyst layer" is used as a general term for the first catalyst layer and the second catalyst layer.

[0011] When the electrode catalyst layer of the present invention is incorporated into an electrochemical cell, the electrode catalyst layer is used such that the first catalyst layer in the electrode catalyst layer is disposed closer to the electrolyte membrane than the second catalyst layer. For example, the first catalyst layer is disposed so as to be in direct contact with the electrolyte membrane. In this case, it is preferable that no other catalyst layer or layer other than the catalyst layer is intentionally formed between the first catalyst layer and the electrolyte membrane. However, if necessary, the other catalyst layer or layer other than the catalyst layer may be disposed between the first catalyst layer and the electrolyte membrane. Regarding the second catalyst layer, for example, the second catalyst layer may be in direct contact with the gas diffusion layer, or another layer, such as a microporous layer, may be interposed between the second catalyst layer and the gas diffusion layer.

[0012] The first catalyst layer is configured to include a first catalyst-supported carrier in which a first catalytically active component is supported on a carrier containing a first metal oxide. Meanwhile, the second catalyst layer is configured to include a second catalyst-supported carrier in which a second catalytically active component is supported on a carrier containing a second metal oxide. The first catalyst layer and the second catalyst layer are configured to be separated by, for example, the particle diameter (e.g., volume cumulative particle diameter D 50 ) Alternatively, the first catalyst layer and the second catalyst layer may be distinguished by the type of catalytically active component or the type of carrier. Alternatively, the first catalyst layer and the second catalyst layer may be distinguished by their physical properties, for example, cell resistance.

[0013] In the present invention, the first and second catalyst layers constituting the electrode catalyst layer each have a different function. Specifically, the first catalyst layer has a function of suppressing a decrease in electrochemical reaction even when the inside of the electrode catalyst layer is in a low-humidity state. On the other hand, the second catalyst layer has a function of suppressing a decrease in the electrochemical reaction even when the inside of the electrode catalyst layer is in a highly humid state, and as a result, the electrode catalyst layer of the present invention can smoothly proceed with the electrochemical reaction in both a low-humidity state and a high-humidity state. Furthermore, in the present invention, since a metal oxide is used as a support for the catalytically active component, the durability during power generation is high. In the present invention, the term "low humidity state" refers to a state in which the humidity in the electrode catalyst layer is approximately 40% RH or less, whereas the term "high humidity state" refers to a state in which the humidity in the electrode catalyst layer is approximately 90% RH or more.

[0014] It is known that the proton mobility of the electrolyte membrane and ionomer is affected by the humidity level in the electrode catalyst layer, which in turn affects the electrochemical reaction. In particular, proton mobility is likely to decrease in a low humidity state. The present inventors have conducted extensive research from the perspective of suppressing the decrease in proton mobility in the electrode catalyst layer in a low humidity state, and have found that it is effective to configure each catalyst layer so that the cell resistance of the first catalyst layer is lower than the cell resistance of the second catalyst layer. There are various factors that make up the cell resistance, such as the resistance of the electrolyte membrane, the electrical resistance of the constituent members, contact resistance, etc., but the main factor is proton mobility. Therefore, in the present invention, the cell resistance is used as a measure of proton mobility, and the cell resistance of each catalyst layer is adjusted to allow the electrochemical reaction to proceed smoothly in both low and high humidity conditions.

[0015] In order to allow the electrochemical reaction to proceed more smoothly under both low and high humidity conditions, at 80°C and 40% RH, the cell resistance R1 of the first catalytic layer is preferably 50% or more and less than 100% of the cell resistance R2 of the second catalytic layer, more preferably 70% or more and 95% or less, and even more preferably 80% or more and 92% or less.

[0016] The cell resistance of the first and second catalyst layers is measured under low humidity conditions at 80°C and 40% RH. A current interruption method is used to measure the cell resistance. A single cell is fabricated using the first or second catalyst layer as the cathode electrode catalyst and platinum-supported carbon as the anode electrode catalyst, and the cell resistance is measured for the single cell. A detailed method for measuring the cell resistance will be explained in the examples below.

[0017] As described above, the cell resistance of the first catalyst layer is preferably lower than that of the second catalyst layer under low humidity conditions of 80°C and 40% RH, and is also advantageously lower than that of the second catalyst layer under high humidity conditions of 80°C and 90% RH, since this allows the electrochemical reaction to proceed more smoothly under both low and high humidity conditions. In particular, at 80°C and 90% RH, the cell resistance R1 of the first catalyst layer is preferably 50% or more and less than 100% of the cell resistance R2 of the second catalyst layer, more preferably 70% or more and 95% or less, and even more preferably 80% or more and 92% or less.

[0018] The first catalyst layer and the second catalyst layer constituting the electrode catalyst layer of the present invention will be described below. The first catalyst layer includes a first catalyst-supporting carrier, which is configured by supporting a first catalytically active component on a carrier containing a first metal oxide. The first metal oxide is preferably a metal oxide having electrical conductivity, and is preferably a metal oxide in which dissolution of the metal constituting the first metal oxide is unlikely to occur during operation of the electrochemical cell.

[0019] The first metal oxide preferably has a volume resistivity of, for example, 100 kΩcm or less. The volume resistivity is measured, for example, using a powder resistivity measurement system (Mitsubishi Chemical Analytech PD-51) and a resistivity measurement device (Mitsubishi Chemical Analytech MCP-T610). Specifically, 1 g of sample is placed in a probe cylinder, and the probe unit is set in the PD-51. A load of 18 kN is applied by a hydraulic jack to produce a cylindrical pellet with a diameter of 20 mm. The resistance value of the obtained pellet is measured using the MCP-T610.

[0020] Examples of the first metal oxide include one or more selected from indium oxide, tin oxide, titanium oxide, zirconium oxide, cerium oxide, molybdenum oxide, tungsten oxide, zinc oxide, vanadium oxide, tantalum oxide, niobium oxide, and rhenium oxide. In particular, the first metal oxide is preferably tin oxide, titanium oxide, or zirconium oxide, since it has excellent acid resistance. More preferred inorganic oxides include, for example, tin oxide containing one or more elements selected from indium, niobium, tantalum, antimony, and tungsten. Also, tin oxide containing a halogen element may be included. Specifically, metal or non-metal-containing (doped) tin oxide such as indium-containing tin oxide, antimony-containing tin oxide, fluorine-containing tin oxide, fluorine-tungsten-containing tin oxide, tantalum-containing tin oxide, tantalum-antimony-containing tin oxide, tungsten-containing tin oxide, and niobium-containing tin oxide may be included.

[0021] As the support made of tin oxide, specifically, those described in WO2016 / 98399 and WO2020 / 31479 can be used. The contents of these publications are incorporated herein by reference.

[0022] The primary particle size of the first metal oxide is preferably 10 nm to 100 nm, particularly 10 nm to 50 nm, and especially 12 nm to 50 nm, in order to increase the specific surface area of ​​the support and to support the catalyst with high dispersion. The particle size of the first metal oxide is determined by observing the metal oxide particles with an electron microscope, measuring the maximum transverse length of 500 or more particles, and calculating the average value. The observation magnification is 100,000 times, and the measurement is performed on an object that is recognized as the smallest unit of a particle based on its apparent geometric shape at that magnification.

[0023] The first catalytically active component supported on the carrier made of the first metal oxide can be the same as that used in the art. For example, various precious metals can be used as the first catalytically active component. In particular, it is preferable to use at least one element selected from the group consisting of platinum, palladium, ruthenium, osmium, and iridium as the first catalytically active component because of its high catalytic activity, and it is more preferable to use platinum.

[0024] When platinum is used as the first catalytic active component, platinum alone or a platinum alloy can be used. Examples of platinum alloys include alloys of platinum and precious metals other than platinum, and alloys of platinum and transition metals. Examples of precious metals other than platinum include palladium, ruthenium, rhodium, osmium, and iridium. Examples of transition metals include nickel, cobalt, iron, manganese, chromium, molybdenum, lanthanum, cerium, gadolinium, copper, and titanium. When platinum is used as the first catalytically active component, it is preferable to use platinum alone, since the catalytic activity is particularly high even when the inside of the electrode catalyst layer is in a low-wet state.

[0025] The first catalytically active component preferably has an average particle size of 1 nm or more and 10 nm or less on the surface of the carrier in terms of efficient expression of catalytic activity. The particle size of the catalyst can be measured in the same manner as the particle size of the first metal oxide. The observation magnification is 500,000 times.

[0026] The volume cumulative particle size D of the first catalyst-supporting carrier at 50% cumulative volume by a laser diffraction / scattering particle size distribution measurement method 50 is preferably 0.1 μm or more and 8 μm or less, more preferably 0.2 μm or more and 5 μm or less, and even more preferably 0.3 μm or more and 3 μm or less. The first catalyst-supporting carrier may be used in a powder state or may be granulated by a method such as spray drying, extrusion granulation, or rolling granulation. In addition, the above-mentioned D 50 For example, a dispersion liquid in which a catalyst layer composition containing a catalyst-supporting carrier and an ionomer such as Nafion (registered trademark) described later is dispersed is diluted with ethanol, and the measurement can be performed using a laser diffraction / scattering particle size distribution device. In place of a measurement method targeting a dispersion liquid, the catalyst can be peeled off from a Teflon (registered trademark) sheet or a catalyst-coated electrolyte membrane (hereinafter also referred to as "CCM") after coating, and the peeled catalyst-supporting carrier can be dispersed in ethanol for measurement.

[0027] In particular, when the first catalyst-supporting carrier is used in a granulated state, it is easy to control the amount of water present in the first catalyst layer, and there is an advantage that the proton mobility is unlikely to decrease even if the inside of the electrode catalyst layer becomes in a low-humidity state. From this viewpoint, the volume cumulative particle diameter D 50 is preferably in the above range.

[0028] Next, the second catalyst layer will be described. The second catalyst layer contains a second catalyst-supporting carrier. The second catalyst-supporting carrier is formed by supporting a second catalytic active component on a carrier containing a second metal oxide.

[0029] As the second metal oxide, a metal oxide having electrical conductivity is preferably used. As the second metal oxide, a metal oxide in which the metal constituting the second metal oxide is unlikely to dissolve during the operation of the electrochemical cell is preferably used. Specifically, as the second metal oxide, the same or different type of oxide as those exemplified as the first metal oxide can be used. For example, as the first metal oxide and the second metal oxide, tin oxide, titanium oxide, or zirconium oxide can be used independently.

[0030] The second catalytically active component supported on the carrier made of the second metal oxide may be the same as that used in the art. For example, various precious metals may be used as the second catalytically active component. Specifically, the second catalytically active component may be the same as or different from the first catalytically active component. In detail, it is preferable that the first catalytically active component and the second catalytically active component each independently contain at least one element selected from the group consisting of platinum, palladium, ruthenium, osmium, and iridium.

[0031] In particular, it is preferable to use a platinum-transition metal alloy as the second catalytically active component, since it is easy to adjust the cell resistance of the first catalytic layer to be lower than the cell resistance of the second catalytic layer. The use of a platinum-transition metal alloy is also preferable in terms of high catalytic activity. A platinum-transition metal alloy is a preferable material because it has a higher catalytic activity than platinum alone, but on the other hand, a decrease in catalytic activity in low-humidity conditions may be observed. However, by arranging the platinum-transition metal alloy in the second catalytic layer, i.e., on the side relatively far from the electrolyte membrane, water is smoothly supplied from the first catalytic layer (i.e., proton mobility is not reduced), so that catalytic activity is less likely to decrease.

[0032] From the viewpoint of maximizing catalytic activity, the ratio of platinum to the transition metal in the platinum-transition metal alloy is preferably 20 mol % or more and 40 mol % or less of the transition metal relative to 100 mol % of platinum.

[0033] The preferred particle size of the second catalyst-supporting carrier is the same as that of the first catalyst layer. The second catalyst-supporting carrier may be used in a powder state or in a granulated state.

[0034] In order to make the cell resistance of the first catalytic layer lower than the cell resistance of the second catalytic layer, for example, one or a combination of two or more of the following may be adopted: (i) making the second catalytic active component different from the first catalytic active component, (ii) making the particle size of the first catalyst-supported carrier larger than the particle size of the second catalyst-supported carrier, (iii) adjusting the pore size distributions of the first catalytic layer and the second catalytic layer, and (iv) making the amount of ionomer contained in the first catalytic layer different from the amount of ionomer contained in the second catalytic layer. In the case of (i), it is preferable to use, for example, platinum alone as the first catalytically active component, while using a platinum-transition metal alloy as the second catalytically active component. In the case of (ii), the volume cumulative particle size D at 50% by volume of the first catalyst-supporting carrier measured by a laser diffraction / scattering particle size distribution measurement method is 50 The volume cumulative particle size D at 50% of the cumulative volume of the second catalyst-supporting carrier measured by a laser diffraction / scattering particle size distribution measurement method 50 It is advantageous to make it larger than In the case of (iii), it is advantageous that, in the pore size distribution measured by mercury intrusion porosimetry, the first catalytic layer has peaks in the range of 0.005 μm or more and less than 0.1 μm and in the range of 0.1 μm or more and 1 μm or less, and the second catalytic layer has at least one peak in the range of 0.005 μm or more and 0.1 μm or less. For the purposes of (ii) and (iii), it is preferred to use a granulated first catalyst-supporting carrier and a powdered second catalyst-supporting carrier. In the case of (iv), the amount of the ionomer contained in the first catalyst layer is preferably greater than the amount of the ionomer contained in the second catalyst layer. The above-mentioned techniques (i)-(iv) can be applied whether the first metal oxide and the second metal oxide are the same or different, but are particularly effective when the first metal oxide and the second metal oxide are the same, and are particularly effective when both the first metal oxide and the second metal oxide are tin oxide.

[0035] The first catalyst layer and the second catalyst layer may contain other components in addition to the catalyst-supporting carrier. The first catalyst layer and / or the second catalyst layer may contain, for example, an ionomer. The ionomer preferably has proton conductivity. By containing an ionomer in the first catalyst layer and / or the second catalyst layer, the performance of these catalyst layers is further improved. As the ionomer, for example, a polymer material having a structure in which a perfluoroether pendant side chain having a sulfonic acid group at the end is bonded to a polytetrafluoroethylene main chain can be used. As such an ionomer, for example, Nafion (registered trademark), Flemion (registered trademark), Aciplex (registered trademark), Fumion F (registered trademark), etc. can be mentioned.

[0036] When the first catalyst layer and / or the second catalyst layer contain an ionomer, it is advantageous to adjust the amount of the ionomer and the amount of the carrier in order to make the cell resistance of the first catalyst layer lower than that of the second catalyst layer. For example, in the first catalyst layer and / or the second catalyst layer, from the viewpoint of easily adapting to humidity changes by coating the catalytic active component or the catalyst-supporting carrier with an ionomer, the value of I / M, which is the ratio of the mass I of the ionomer to the mass M of the carrier of the first catalyst layer or the carrier of the second catalyst layer, is preferably 0.06 or more, and more preferably 0.07 or more. On the other hand, from the viewpoint of suppressing the increase in cell resistance due to the high proportion of the ionomer, the value of I / M is preferably 0.25 or less, more preferably 0.22 or less, and even more preferably 0.20 or less. Note that the ionomer is often provided in the form of a dispersion, and the mass I of the ionomer refers to the mass of the solid content in the dispersion.

[0037] The thickness t1 of the first catalyst layer is preferably 0.2 μm or more and 10 μm or less. By setting the thickness t1 of the first catalyst layer in this range, not only can the resistance of the catalyst layer be reduced even in a low humidity state, but also flooding phenomenon in a high humidity state can be effectively prevented. From this viewpoint, the thickness t1 of the first catalyst layer is more preferably 0.5 μm or more and 7.5 μm or less, and even more preferably 1 μm or more and 5 μm or less.

[0038] On the other hand, the thickness t2 of the second catalytic layer is preferably 0.5 μm or more and 15 μm or less. By setting the thickness t2 of the second catalytic layer in this range, the flooding phenomenon in a highly humid state can be prevented, and good catalytic activity can be obtained, which is preferable. From this viewpoint, the thickness t2 of the second catalytic layer is more preferably 2 μm or more and 10 μm or less, and even more preferably 2 μm or more and 8 μm or less.

[0039] The relative relationship between the thickness t1 of the first catalytic layer and the thickness t2 of the second catalytic layer is related to the smooth progress of electrochemical reactions in a low humidity state and in a high humidity state. From this viewpoint, the value of t1 / t2, which is the ratio of the thickness t1 of the first catalytic layer to the thickness t2 of the second catalytic layer, is preferably set to 0.05 to 2, more preferably 0.1 to 1.5, even more preferably 0.2 to 1, and even more preferably 0.4 to 0.9.

[0040] The thickness of each of the first and second catalyst layers is measured as follows. The first and second catalyst layers are formed in order on the solid electrolyte membrane, and the cross section is observed with a scanning electron microscope at a magnification of, for example, 5000 times. The thicknesses of the first and second catalyst layers are measured at 20 points at arbitrary intervals within the observation field of the image. Next, two cross-sectional images are taken at positions different from the previous one, and the average thicknesses of the first and second catalyst layers are calculated in the same manner. Finally, the thicknesses of the first and second catalyst layers are calculated by arithmetically averaging the thicknesses of the first and second catalyst layers at 60 points each measured during the three-point image observation.

[0041] In order to make the cell resistance of the first catalytic layer lower than that of the second catalytic layer, it is also advantageous to adjust the pore size distribution in these catalytic layers. In particular, for the first catalytic layer, it is preferable that at least one peak is observed in the range of 0.005 μm or more and less than 0.1 μm in the pore size distribution measured by mercury intrusion porosimetry. It is particularly preferable that a single peak is observed in this pore size range. In the first catalyst layer, in addition to the above range, it is preferable that at least one peak is observed in the range of 0.1 μm to 1 μm, and it is particularly preferable that a single peak is observed in this pore size range. In order to make the pore size distribution of the first catalytic layer have peaks in the above-mentioned ranges, it is advantageous to use, for example, a first metal oxide constituting the first catalyst-supporting carrier having a particle size of 10 nm or more and 100 nm or less, and to use the first catalyst-supporting carrier in a granulated state. The peak in the range of 0.005 μm or more and less than 0.1 μm mainly corresponds to the pores between the primary particles of the first catalyst-supporting carrier. The peak in the range of 0.1 μm or more and 1 μm or less mainly corresponds to the pores between the granules.

[0042] On the other hand, for the second catalyst layer, in the pore size distribution measured by mercury intrusion porosimetry, it is preferable that at least one peak is observed in the range of 0.005 μm or more and 0.1 μm or less, and it is more preferable that a single peak is observed. In order to make the pore size distribution of the second catalytic layer have a single peak in the above-mentioned range, it is advantageous to use the second metal oxide constituting the second catalyst-supporting carrier having a particle size of 10 nm or more and 100 nm or less, and to use the second catalyst-supporting carrier in a powder state (i.e., without granulation).

[0043] The pore size distribution by mercury intrusion porosimetry is measured, for example, using an AutoPore IV Model 9520 manufactured by Shimadzu Corporation. In detail, a measurement sample is placed in a cell, and pressure is continuously applied from 0 psi to 60,000 psi (413,700 kPa), and the amount of mercury intruded into the pores of the sample is estimated from the electrostatic capacitance to obtain the relationship between the pore size and the pore volume.

[0044] The electrode catalyst layer of the present invention can be used as a CCM of an electrochemical cell. The CCM comprises a solid electrolyte membrane and an electrode catalyst layer disposed on the surface of the solid electrolyte membrane. In the electrode catalyst layer of this CCM, the first catalyst layer is disposed closer to the solid electrolyte membrane than the second catalyst layer.

[0045] Examples of solid electrolyte membranes include perfluorosulfonic acid polymer-based proton conductor membranes, membranes in which inorganic acids such as phosphoric acid are doped into hydrocarbon polymer compounds, organic / inorganic hybrid polymers in which a portion of the polymer is substituted with functional groups of a proton conductor, and proton conductors in which a polymer matrix is ​​impregnated with a phosphoric acid solution or a sulfuric acid solution.

[0046] To obtain a CCM by forming an electrode catalyst layer having a first catalyst layer and a second catalyst layer on the surface of a solid electrolyte membrane, a dispersion containing a first catalyst-supporting carrier is first prepared, and the dispersion is applied to one side of a release sheet to form a coating of the first catalyst layer. Next, the surface of the release sheet to which the dispersion is applied and the solid electrolyte membrane are overlapped, and in this state, the first catalyst layer is transferred to the solid electrolyte membrane by heat pressing. Subsequently, a dispersion containing a second catalyst-supporting carrier is applied to one side of the release sheet to form a coating of the second catalyst layer. Then, the surface of the release sheet to which the dispersion is applied and the surface of the solid electrolyte membrane on which the first catalyst layer is formed are overlapped, and in this state, the second catalyst layer is transferred to the first catalyst layer by heat pressing. This obtains a CCM.

[0047] As the liquid medium used to prepare the dispersion of the catalyst-supported carrier, it is preferable to use a primary alcohol. Examples of the primary alcohol include those having 1 to 10 carbon atoms. Among these, it is preferable to use a saturated aliphatic alcohol. Examples include methanol, ethanol, propanol, butanol, pentanol, hexanol, heptanol, octanol, nonanol, and decanol. In particular, it is preferable to use a saturated aliphatic alcohol having 1 to 4 carbon atoms. The primary alcohol can be used alone or in combination of two or more. In addition, other solvents than the above-mentioned primary alcohols, such as aliphatic monohydric alcohols such as 2-propanol, aromatic hydrocarbons such as toluene and benzene, aliphatic hydrocarbons such as hexane, other organic solvents such as ketones, esters, and ethers, and water can also be used.

[0048] The electrode catalyst layer of the present invention can also be used as a membrane electrode assembly (hereinafter also referred to as "MEA"). The MEA comprises a solid electrolyte membrane, an electrode catalyst layer arranged on the surface of the solid electrolyte membrane, and a gas diffusion layer arranged on the surface of the electrode catalyst layer. In the electrode catalyst layer of this MEA, the first catalyst layer is arranged closer to the solid electrolyte membrane than the second catalyst layer.

[0049] The gas diffusion layer may be, for example, a porous material such as carbon paper or carbon cloth. Specifically, the gas diffusion layer may be formed of carbon cloth woven with a predetermined ratio of carbon fibers whose surfaces are coated with polytetrafluoroethylene and carbon fibers that are not coated.

[0050] An electrochemical cell can be assembled using the above-mentioned MEA. When the electrochemical cell is a battery, for example a fuel cell or a metal-air battery, the electrode catalyst layer of the present invention is preferably used as a cathode. When the electrochemical cell is a water electrolysis device, the electrode catalyst layer of the present invention is preferably used as an anode. This is preferable in that the electrochemical reaction can be smoothly carried out in both low and high humidity conditions. EXAMPLES

[0051] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".

[0052] Example 1 (1) Preparation of the first metal oxide An alkaline aqueous solution was prepared by dissolving 5.47g of sodium hydroxide and 0.56g of Na2WO4·2H2O in 495g of pure water. This is Liquid A. Separately, 489g of pure water was placed in a beaker, and 11.55g of stannous fluoride was dissolved in it to obtain a tin aqueous solution. This is Liquid B. While stirring Liquid B with a paddle blade at room temperature (25°C), the entire amount of Liquid A prepared earlier was poured into it. After the addition of Liquid A was completed, aging was carried out at room temperature while stirring for 5 minutes. After that, decantation washing was performed using pure water until the pH reached 100μS / cm or less, and a precursor slurry was obtained.

[0053] The resulting slurry was adjusted to a concentration of 1% by adding pure water, and 200 g of this was weighed out. 1.07 g of 30% hydrogen peroxide solution was added thereto. The mixture was then aged at room temperature for 5 minutes while stirring.

[0054] Hydrothermal synthesis was carried out using the apparatus shown in FIG. 1 of WO2016 / 98399. The set temperature of the reactor 10 in the figure was 600°C. The pressure in the reactor 10 was 25 MPa. This temperature and pressure condition was the supercritical condition of water. The length of the pipe from the mixing section 8 to the outlet of the reactor 10 in the figure and the pump flow rate were adjusted so that the reaction time was 5 minutes. In this way, tin oxide particles containing fluorine and tungsten were obtained. These tin oxide particles were used as the first metal oxide. As a result of observation with an electron microscope, the primary particle size of these tin oxide particles was 15 nm.

[0055] (2) Granulation of the first metal oxide The first metal oxide obtained in (1) was granulated by a spray dry method. The operating conditions of the spray dryer were as follows: Slurry concentration: 40g / L Slurry supply rate: 3.3mL / min ·Inlet temperature: 220℃ The volume cumulative particle size of the obtained granules D 50 was 2.45 μm.

[0056] (3) Preparation of the first catalyst-supporting carrier 5mL of HPtCl6 solution (equivalent to 1g of Pt) was dissolved in 295mL of distilled water, 15.3g of NaHSO3 was added, and then diluted with 1400mL of distilled water. 5% NaOH aqueous solution was added to adjust the pH to about 5, while 35% hydrogen peroxide solution (120mL) was added dropwise to obtain a solution containing platinum colloid. At this time, 5% NaOH aqueous solution was appropriately added to maintain the pH of the solution at about 5. 5.67g of the tin oxide particles obtained in (2) was added and mixed at 90°C for 3 hours. After that, the solution was cooled and further separated into solid and liquid. In order to remove chloride ions from the water-containing powder obtained by solid-liquid separation, it was diluted again with 1500mL of distilled water and boiled at 90°C for 1 hour, the solution was cooled and separated into solid and liquid. This washing process was carried out four times. Finally, after solid-liquid separation, it was dried in air at 60°C for 12 hours. This resulted in platinum containing non-stoichiometric platinum oxide being supported on the surface of the tin oxide particles. The tin oxide particles were then heat-treated at 80°C for 2 hours in a 4 vol% H2 / N2 atmosphere to reduce the platinum. The amount of platinum supported, as measured by ICP emission spectrometry, was 14% relative to the platinum-supported tin oxide particles. In this way, a first catalyst-supporting carrier was obtained.

[0057] (4) Formation of the first catalyst layer 1.46 g of the first catalyst-supported carrier made of granules was placed in a container, and pure water, ethanol, and 2-propanol were added in order in a mass ratio of 35:45:20 (3.06 g as a mixed liquid). The dispersion thus obtained was dispersed by ultrasonic waves for 3 minutes. Next, a 10 mm diameter yttrium-stabilized zirconia ball was placed in the container, and the mixture was stirred at 800 rpm for 20 minutes using a planetary ball mill (Thinky ARE310). 5% Nafion (registered trademark) (274704-100ML, manufactured by Sigma-Aldrich) was further added to the dispersion, and the same stirring as above was performed using ultrasonic dispersion and a planetary ball mill. The amount of Nafion added was such that the mass ratio of Nafion / (first carrier) was 0.074. The dispersion thus obtained was applied onto a polytetrafluoroethylene sheet using a bar coater, and the coating was dried at 60°C.

[0058] (5) Preparation of the second metal oxide It was prepared in the same manner as in the preparation of the first metal oxide.

[0059] (6) Preparation of the second catalyst-supporting carrier A 500 mL volumetric flask was charged with 337 mL of N,N-dimethylformamide (hereinafter referred to as "DMF"; 049-32363, Fujifilm Wako Pure Chemical Industries, Ltd.), and the following components were further added to the flask at the concentrations shown below. Bis(acetylacetonato)platinum(II) (Pt(acac)2, 028-16853, Fujifilm Wako Pure Chemical Industries, Ltd.): 9.87 × 10 -3 mol / L -DMF Bis(2,4-pentanedionato)nickel(II) dihydrate (Ni(acac)2 2H2O, 343-01981, Dojindo Laboratories): 3.62 × 10 -3 mol / L -DMF Benzoic acid (204-00985, Fujifilm Wako Pure Chemical Industries): 2.49 x 10 -1 mol / L -DMF The second metal oxide obtained in (5): 7.49 g / L -DMF The liquid obtained by mixing the above-mentioned components was dispersed at room temperature for 30 minutes using an ultrasonic disperser to obtain a dispersion. While purging the inside of a measuring flask containing the dispersion with argon gas, preliminary stirring was performed at room temperature for 20 hours at 400 rpm using a rugby ball-shaped stirrer with a major axis of about 2 cm and a minor axis of about 1 cm.

[0060] Next, the volumetric flask containing the dispersion liquid that had been subjected to the pre-stirring was immersed in an oil bath with the oil temperature controlled at 160°C while being kept purged with argon gas, and the dispersion liquid was heated. At this time, it took about 7 minutes for the solvent in the volumetric flask to boil. After boiling, the oil temperature in the oil bath was controlled at 160°C and the mixture was heated under reflux for 12 hours. After that, the oil bath was removed and the mixture was cooled to room temperature, and then filtered to obtain a solid content. The obtained solid was washed five times with a mixed solvent of acetone and ethanol (volume ratio 1:1), then washed once with a mixed solvent of water and ethanol (volume ratio 1:1), and then dried. The obtained dried powder was dispersed in 400 mL of 0.5 mol / L perchloric acid, heated and stirred at 60°C for 2 hours, and then filtered, washed, and dried. In this way, a second catalyst support on which a platinum-nickel alloy was supported was obtained. The amount of the platinum-nickel alloy supported on the second catalyst support was 20% platinum and 1.6% nickel relative to the second catalyst support (containing 26.6 mol % nickel relative to 100 mol % platinum).

[0061] (7) Formation of the second catalyst layer 1.0 g of the second catalyst-supported carrier was placed in a container, and pure water, ethanol, and 2-propanol were added in that order in a mass ratio of 33:50:17 (2 g as a mixed liquid). The dispersion thus obtained was dispersed by ultrasonic waves for 3 minutes. Next, a glass ball with a diameter of 2 mm was placed in the container, and the mixture was stirred at 100 rpm for 30 minutes using a planetary ball mill (PM 200, manufactured by Retsch). Furthermore, 5% Nafion (registered trademark) (274704-100ML, manufactured by Sigma-Aldrich) was added to the dispersion, and the same stirring as above was performed using ultrasonic dispersion and a planetary ball mill. The amount of Nafion added was such that the mass ratio of Nafion / (second carrier) was 0.074. The dispersion thus obtained was applied onto a polytetrafluoroethylene sheet using a bar coater, and the coating was dried at 60°C.

[0062] (8) Formation of an electrode catalyst layer for the anode 1.00 g of platinum-supported carbon black (TEC10E50E) manufactured by Tanaka Kikinzoku Kogyo Co., Ltd. was placed in a container, and pure water, ethanol, and 2-propanol were added in order in a mass ratio of 45:35:20 (12.8 g as a mixed solution). The dispersion thus obtained was dispersed by ultrasonic waves for 3 minutes. Next, a 10 mm diameter yttrium-stabilized zirconia ball was placed in the container, and the mixture was stirred at 800 rpm for 20 minutes by a planetary ball mill (Thinky ARE310). 5% Nafion (registered trademark) (274704-100ML, manufactured by Sigma-Aldrich) was further added to the dispersion, and the same stirring as above was continued by ultrasonic dispersion and planetary ball mill. The amount of Nafion added was such that the mass ratio of Nafion / platinum-supported carbon black was 0.70. The dispersion thus obtained was coated on a polytetrafluoroethylene sheet using a bar coater, and the coating was dried at 60°C.

[0063] (9) Manufacturing of CCM The first catalyst layer-attached polytetrafluoroethylene sheet and the anode catalyst layer-attached polytetrafluoroethylene sheet were cut into squares measuring 54 mm on each side, and placed on top of a Nafion (registered trademark) (NRE-211, DuPont) electrolyte membrane. The resulting mixture was then heated at 140° C. and 20 kgf / cm 2 The polytetrafluoroethylene sheet with the first catalyst layer was then peeled off to expose the first catalyst layer, and the polytetrafluoroethylene sheet with the second catalyst layer was then placed on top of the first catalyst layer. 2 The transfer was performed by heat pressing in the atmosphere for 2 minutes under the condition of 0.1 μm to 1.0 μm. In this manner, a cathode catalyst layer consisting of the first catalyst layer and the second catalyst layer was formed on one surface of the solid polymer electrolyte membrane made of Nafion, and an anode catalyst layer was formed on the other surface.

[0064] (10) Assembly of polymer electrolyte fuel cells A polymer electrolyte fuel cell was assembled using the CCM obtained in (9). SIGRACET (registered trademark) 29BC (manufactured by SGL) was used as the gas diffusion layer.

[0065] Example 2 In the (4) forming step of the first catalyst layer in Example 1, the ball diameter was 5 mm, the stirring time before adding 5% Nafion was 90 minutes, and the stirring time after adding it was 60 minutes, so that the granulated first catalyst-supporting carrier was pulverized. A solid polymer electrolyte fuel cell was obtained in the same manner as in Example 1 except for this.

[0066] Comparative Example 1 A polymer electrolyte fuel cell was obtained in the same manner as in Example 1, except that (2) the first metal oxide was not subjected to the granulation step.

[0067] Comparative Example 2 The step (9) of Example 1 was carried out as follows. A polymer electrolyte fuel cell was obtained in the same manner as in Example 1 except for the above. The polytetrafluoroethylene sheet with the second catalyst layer and the polytetrafluoroethylene sheet with the anode electrode catalyst layer prepared in Example 1 were cut into squares of 54 mm on each side, and were superimposed on an electrolyte membrane of Nafion (registered trademark) (NRE-211, manufactured by DuPont). The resulting mixture was then heated at 140° C. and 20 kgf / cm 2 The transfer was performed by heat pressing in the atmosphere for 2 minutes under the condition of 140° C., 20 kgf / cm. The polytetrafluoroethylene sheet with the first catalyst layer prepared in Example 1 was then placed on top of the second catalyst layer, and the transfer was performed by heat pressing in the atmosphere for 2 minutes under the condition of 140° C., 20 kgf / cm. 2 The transfer was performed by heat pressing in the atmosphere for 2 minutes under the condition of: In this manner, a cathode catalyst layer consisting of the second catalyst layer and the first catalyst layer was formed in this order on one surface of the solid polymer electrolyte membrane consisting of Nafion, and an anode catalyst layer was formed on the other surface.

[0068] Comparative Example 3 In this comparative example, the cathode catalyst layer was formed in the same manner as the anode catalyst layer. In other words, the cathode catalyst layer contained a catalyst-supported carrier made of platinum-supported carbon black. A solid polymer electrolyte fuel cell was obtained in the same manner as in Example 1.

[0069] [Rating 1] The particle size distribution of the catalyst-supporting carriers of the first catalyst layer and the second catalyst layer obtained in the examples and comparative examples was measured by the following method. The dispersion liquid used to form the first and second catalyst layers was diluted with ethanol to obtain a liquid, and the particle size distribution was measured using a laser diffraction / scattering type particle size distribution measuring device (LA-920 manufactured by Horiba, Ltd.). The measurement results are shown in Table 1.

[0070] [Rating 2] The cross sections of the CCMs obtained in the examples and comparative examples were observed under an electron microscope to measure the thicknesses of the first and second catalyst layers in the cathode catalyst layer. The pore size distribution was also measured by mercury intrusion porosimetry as described above. The pore size distribution was measured by subjecting the first catalyst layer-attached polytetrafluoroethylene sheet and the second catalyst layer-attached polytetrafluoroethylene sheet obtained in (4) and (7) above to 140°C and 20 kgf / cm2. 2 The first and second catalyst layers were individually formed and subjected to measurement under the conditions of 100° C. and 100° C. for 2 minutes in the atmosphere, and the measurement was performed on the first and second catalyst layers formed separately. The results are shown in Table 1. Note that, for Comparative Example 3, the measurement of the pore size distribution was omitted because the design had only one catalyst layer.

[0071] [Rating 3] The cell resistances of the first and second catalyst layers obtained in the examples and comparative examples were measured by the following method. The results are shown in Table 2. In order to eliminate factors that affect the cell resistance under low humidity conditions other than the characteristics of the catalyst support used in each catalyst layer, the amount of Pt applied to the polytetrafluoroethylene sheet was set to 0.2 mg / cm. 2 was adjusted to. Next, using this sheet with the adjusted coating amount, a single cell for measuring the cell resistance was produced in the following manner. The polytetrafluoroethylene sheet coated with the first catalyst layer and the polytetrafluoroethylene sheet with the anode electrode catalyst layer were cut into squares measuring 54 mm on each side, and placed on top of a Nafion (registered trademark) (NRE-211, DuPont) electrolyte membrane. The resulting mixture was then heated at 140°C and 20 kgf / cm 2The CCM thus obtained was used to assemble a single cell for measuring the cell resistance of the first catalyst layer. SIGRACET (registered trademark) 29BC (manufactured by SGL) was used as the gas diffusion layer. Moreover, a single cell for measuring the cell resistance of the second catalyst layer was assembled in the same manner as described above, using a second catalyst layer-attached polytetrafluoroethylene sheet in place of the first catalyst layer-attached polytetrafluoroethylene sheet. Power was generated using each of the obtained single cells, and the cell resistance at 0.6V power generation was measured by the current interruption method. For the measurements, an 890e-type FC electronic loader manufactured by Scrinber Associates was used. Power generation was performed under high humidity conditions (both cathode and anode at 80°C and 90% RH) and low humidity conditions (both cathode and anode at 80°C and 40% RH). The gases supplied to the anode were hydrogen at 5 L / min and air at 25 L / min to the cathode.

[0072] [Rating 4] The durability at high temperatures of the fuel cells obtained in the examples and comparative examples was measured by the following method. The results are shown in Table 2. Power generation was performed for 16 hours under low humidity conditions (both the cathode and anode were kept at 110°C and 30% RH). The surface area of ​​the platinum catalyst in the electrode catalyst layer was measured by ECSA before and after power generation. F -S A ) / S A The remaining rate (%) of the platinum catalyst was calculated from S × 100, and this value was used as a measure of durability at high temperatures. A represents the surface area of ​​the platinum catalyst before power generation, and S F represents the surface area of ​​the platinum catalyst after power generation.

[0073] [Rating 5] A single cell for measuring the cell resistance was assembled using the CCMs obtained in the examples and comparative examples. SIGRACET (registered trademark) 29BC (manufactured by SGL) was used as the gas diffusion layer. Using each of the obtained single cells, power generation evaluation was performed under high humidity conditions (both cathode and anode at 80°C and 90% RH) and low humidity conditions (both cathode and anode at 80°C and 40% RH). The gas supply to the anode and cathode was 5 L / min for hydrogen to the anode and 25 L / min for air to the cathode. Here, the current density (A / cm) at a voltage of 0.6 V was 2 The calculation results are shown in Table 2.

[0074] [Table 1]

[0075] [Table 2]

[0076] As is clear from the results shown in Table 2, the fuel cells obtained in each Example have excellent durability when generating electricity under high temperature and low humidity conditions. In addition, the fuel cells obtained in each Example exhibit good power generation characteristics under both low humidity and high humidity conditions. [Industrial Applicability]

[0077] The electrode catalyst layer for an electrochemical cell of the present invention is durable and allows electrochemical reactions to proceed smoothly under both low and high humidity conditions.

Claims

1. a first catalyst layer including a first catalyst-supported support in which a first catalytic active component is supported on a support including a first metal oxide; a second catalyst layer including a second catalyst-supported support in which a second catalytic active component is supported on a support including a second metal oxide, the cell resistance of the first catalytic layer measured by a current interruption method at 80° C. and 40% RH is lower than the cell resistance of the second catalytic layer; An electrode catalyst layer for an electrochemical cell, wherein a first catalyst layer is disposed closer to an electrolyte membrane than a second catalyst layer.

2. a first catalyst layer including a first catalyst-supported support in which a first catalytic active component is supported on a support including a first metal oxide; a second catalyst layer including a second catalyst-supported support in which a second catalytic active component is supported on a support including a second metal oxide, The volume cumulative particle size D of the first catalyst-supporting carrier at 50% cumulative volume by a laser diffraction / scattering particle size distribution measurement method 50 The volume cumulative particle size D of the second catalyst-supporting carrier at 50% cumulative volume measured by a laser diffraction / scattering particle size distribution measurement method 50 Larger than The pore size distribution measured by mercury intrusion porosimetry was In the first catalyst layer, peaks are observed in the range of 0.005 μm or more and less than 0.1 μm and in the range of 0.1 μm or more and 1 μm or less. At least one peak is observed in the range of 0.005 μm or more and 0.1 μm or less for the second catalyst layer, An electrode catalyst layer for an electrochemical cell, wherein a first catalyst layer is disposed closer to an electrolyte membrane than a second catalyst layer.

3. 3. The electrode catalyst layer according to claim 1, wherein the first catalytically active component and the second catalytically active component each independently contain at least one element selected from the group consisting of platinum, palladium, ruthenium and iridium.

4. The electrocatalyst layer according to claim 3 , wherein the catalytically active component further comprises a transition metal.

5. the first catalytic active component contained in the first catalytic layer is platinum alone; 4. The electrode catalyst layer according to claim 3, wherein the second catalytic active component contained in the second catalyst layer is a platinum-transition metal alloy.

6. 6. The electrocatalyst layer according to claim 1, wherein the first metal oxide and the second metal oxide are each independently tin oxide, titanium oxide or zirconium oxide.

7. Thickness t of the second catalyst layer 2 Thickness t of the first catalyst layer 1 The ratio of t 1 / t 2 The electrode catalyst layer according to claim 1 , wherein the value of is 0.05 or more and 2 or less.

8. Thickness t of the first catalyst layer 1 is 0.2 μm or more and 10 μm or less, Thickness t of the second catalyst layer 2 The electrode catalyst layer according to claim 1 , wherein the thickness is from 0.5 μm to 15 μm.

9. A membrane electrode assembly for an electrochemical cell comprising a solid electrolyte membrane, a catalyst layer disposed on a surface of the solid electrolyte membrane, and a gas diffusion layer disposed on a surface of the catalyst layer, 9. A membrane electrode assembly for an electrochemical cell, wherein the catalyst layer is the electrode catalyst layer according to claim 1.

10. An electrochemical cell comprising the membrane electrode assembly according to claim 9.

11. 11. The electrochemical cell of claim 10 which is a polymer electrolyte fuel cell.

12. 11. The electrochemical cell of claim 10 which is a metal-air battery.

13. 11. The electrochemical cell of claim 10 which is a water electrolysis device.

Citation Information

Patent Citations

  • Fuel cell

    JP2004171847A

  • Membrane electrode assembly for fuel cell, and fuel cell using it

    JP2008176990A

  • Membrane electrode assembly and solid polymer fuel cell in which same is used

    US20170141407A1

  • Fuel cell, membrane-electrode assembly, and membrane-catalyst layer assembly

    WO2009001560A1

  • Membrane electrode assembly, process for producing membrane electrode assembly, solid polymer fuel cell

    WO2009004958A1